Computer literacy and the impact of health information systems on work and quality control in nursing practice - Aleksopulos, Hristos (Medicinski časopis, 2022)
Abstract Health information system includes a wide range of products, technologies and services such as remote and mobile health technology, cloud-based services, medical devices, tele-monitoring devices, assistive and sensor technologies, electronic health records, electronic medical records and other applications of information technologies in healthcare. Objective: To determine whether the method of acquiring IT knowledge affects computer literacy and how the implementation of HIS affects work and quality control. Methodology: The research was conducted as a cross-sectional study, in the population of nurses. The sample consisted of 116 respondents, who voluntarily agreed to participate in the research. Results: Respondents who have formal education in informatics showed a higher level of knowledge than respondents who do not. It was established that there is a statistically significant difference in computer literacy between respondents who acquired IT knowledge in different ways. Those who rated themselves better have higher scores on the knowledge test. The data indicate the existence of statistical significance of differences depending on the self-assessment of one's own computer skills. Almost half (46.7%) of respondents believe that the implementation of HIS made work easier, while 26% of them believe that it had no impact on work or made work more difficult. The largest percentage (59.9%) of respondents believed that the health information system facilitated quality control. Conclusion: The way of acquiring knowledge has the greatest influence on the computer literacy of nurses: nurses who had formal education showed a higher level of computer literacy. Nurses believe that thanks to the implementation of HIS, the quality control of the provided services has been significantly improved. The majority of health workers in the initial stages of introduction, application and development of the health information system had no formal education. Nevertheless, with the support of the institutions, they made a significant contribution to the implementation of HIS in the Republic of Serbia.